Effect of indoor house dust mite concentration on canine atopic dermatitis - Kim, Jihee; Lee, Ji-Hye; Song, Yunji; Kim, Ha-Jung (Frontiers in Veterinary Science, 2023)
House dust mites (HDM) are regarded as essential environmental allergens not only in human, but also in canine atopic dermatitis (CAD), however, there are only a few studies on the influence of indoor HDM concentration on the disease. Our study analyzed the correlation between the indoor HDM concentration, the severity of CAD, and the residential environments in client-owned 35 AD and 13 healthy dogs. We measured the extent of CAD and severity index-04 (CADESI-04), pruritus visual analogue scale (PVAS), and transepidermal water loss (TEWL), indoor relative humidity (RH) and analyzed the residential environment questionnaires to evaluate AD severity. The Der f 1 concentration had an inverse association with TEWL, and no association with CADESI-04 and PVAS. The Der f 1 concentration was significantly high in the group living near the green area and 40% or higher RH. In conclusion, our results suggest two possibilities: (1) Living around green areas and maintaining an appropriate indoor climate may help to improve CAD clinical symptoms. (2) The HDM may contain endotoxin and when present in high concentrations in CAD, they play a preventive role by enhancing the skin barrier function. Further studies with a larger number of dogs may help further elucidate an association between CAD and Der f 1.